(untitled) (MAUSAM, 1984)
In the present paper, a heat budget model developed by Young (1979) which predicts heat stress in humans during exercise is applied to define the maximum recommended duration, of exercise (MRDE) as a function of ambient temperature, relative- humidity, radiation as well as the level of exercise. The model accounts for the generation, dissipation and storage of heat in the body and allows for solar radiation and the effect of clothing, and predicts the skin and core temperatures and dehydration as a function of time under given ambient conditions. The MRDE charts presented in the paper could be used as guides in defining the types of activities that should be restricted under relatively warm and humid climates. Based on these charts, a bio-meteorological classification of India is attempted to delineate regions where different levels of physical activity may be permitted in the different seasons, without exposing the human subjects to the risks of heat exhaustion and heat strokes.